Psychological approaches to obesity in young adults: state of the art - Alves, Rafaela; Petitjean, Hugues; Druzhinenko-Silhan, Daria (Frontiers in Nutrition, 2024)
Background Obesity has become a significant health concern among young adults aged 18–35 years. Addressing this issue is crucial, and exploring psychological treatments and perspectives specifically for this population is essential. Methods This literature review examines psychological treatments for obesity in young adults over the past decade. It focuses on interventions and discussions particularly relevant to this age group. Discussion Research on obesity often overlooks young adults, with most interventions primarily focusing on weight loss and neglecting emotional aspects. Cognitive-behavioral approaches are commonly used for self-regulation and motivation, but psychodynamic perspectives remain underutilized. While group-based methods lack a detailed analysis of benefits, hybrid approaches demonstrate higher engagement compared to technology-only interventions. There is a notable gap in tailoring obesity interventions to meet the unique needs of young adults during this transitional life phase. It’s imperative to shift the focus from merely weight loss to a broader consideration of psychological, emotional, and unconscious factors. Integrating group modalities with psychodynamic approaches might offer additional benefits. Conclusion This review highlights the need for further research into the psychological well-being of young adults with obesity. A more comprehensive approach is required to address their distinct needs and psychological factors.